2020
DOI: 10.1016/j.jpsychores.2020.110282
|View full text |Cite
|
Sign up to set email alerts
|

Stay-at-home circumstances do not produce sleep disorders: An international survey during the COVID-19 pandemic

Abstract: Objective The anxiety-related insomnia and other sleep disorders were mentioned as possible side effects of quarantine and stay-at-home conditions. The questions to be explored were: Are there discernable differences in hours of sleep and sleep habits between the normal operational environment and the stay-at-home condition? and How seriously anxiety-induced insomnia or other sleep disorders may affect individuals during the stay-at-home? Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 25 publications
4
38
1
3
Order By: Relevance
“…However, sleep duration did not change due to the lockdown situation contrary to former findings [ 2 , 18 ]. We assume that this could be a result of differential reactions to the pandemic lockdown in each participant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, sleep duration did not change due to the lockdown situation contrary to former findings [ 2 , 18 ]. We assume that this could be a result of differential reactions to the pandemic lockdown in each participant.…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, studies [ 2 , 17 ] found that social jetlag decreased during the COVID-19 pandemic lockdown, sleep duration increased, and sleep timing was delayed. Findings suggest that sleep duration increased during the lockdown and participants were able to extend their sleeping period as needed and change the timing of their sleep as preferred [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting consideration that emerges from the adolescent studies is that the changes favored by the lockdown seem to make their sleep-wake schedule more physiological. Different investigations reported that, during the confinement, adolescents’ sleep duration increased by approximately 1 hour, their sleep quality improved with less daytime sleepiness, the difference in the sleep duration between weekdays and weekends disappeared and the percentage of nappers decreased[ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the COVID-19-mandated social restrictions have relaxed the social time pressure related to social jetlag so individuals can sleep longer and later. A study on 25,000 Argentinians ( Leone et al, 2020 ), another cross-national study on 3,787 participants ( Rome et al, 2020 ), another study on 7,517 participants from 40 countries ( Korman et al, 2020 ), and another cross-national study involving 11 countries on 14,000 participants ( Roitblat et al, 2020 ) showed that COVID-19 related lockdowns and social restrictions have themselves induced significant delays in chronotype. The current weakening of mismatch #4 (morning social pressure) plus the increase of mismatch #2 (artificial lighting) may have converged in increasing evening orientation, which might further complicate the epidemiological liability of mismatch #3 (nocturnal individuals defying the virus-mitigating social restriction protocols).…”
Section: Evolutionary Mismatches During the Covid-19 Pandemicmentioning
confidence: 99%